Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 5 - Number Theory and the Real Number System - 5.7 Arithmetic and Geometric Sequences - Exercise Set 5.7 - Page 329: 46


General Formula: $a_n=6+(n-1)(3)$ $a_{20} = 63$

Work Step by Step

The formula for the general term (the nth term) of an arithmetic sequence is: $a_n=a_1+(nāˆ’1)d$ where d = common difference $a_1$ = first term $a_n$ = nth term n = term number The given arithmetic sequence has: $a_1=6$ and $d=3$ Substitute these into the given formula above: $a_n = 6 + (n-1)(3)$ Thus, $a_{20} = 6+(20-1)(3) \\a_{20}=6+19(3) \\a_{20}=6+57 \\a_{20}=63$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.